A microfluidic device for electrochemical detection based on thick film and LTCC technologies - Pavoni, S. (2006)
A Low Temperature Cofired Ceramics (LTCC) microfluidic device with an integrated thick film electrochemical detector was designed, manufactured and tested. Standard solutions of Fe(CN)63-/4- and H2O2 were used in the electrochemical measurements. The constructed structure is found to be a useful and inexpensive device for electrochemical analysis.